SI Monitoring Dan Distribusi Pupuk Bersubsidi Pada CV Zildhan Tani Kecamatan Belitang II Berbasis Web - Muhairi; Rahayu Amalia; Nyimas Sopiah; Taqrim Ibadi (PPPM Institut Teknologi Pagar Alam, 2025)
The distribution of subsidized fertilizer is a government program designed to help farmers increase agricultural yields at an affordable cost. However, in practice, the distribution and redemption process often faces various obstacles, such as manual recording, inaccurate allocation data, and a lack of transparency between distributors, retailers, and farmers. Therefore, an integrated information system is needed to facilitate accurate and real-time data management and reporting. This research aims to design and build a web-based information system for subsidized fertilizer distribution and redemption that can be used by administrators, retailers, farmers, and management or business owners. The system was designed using a web engineering approach and developed using the PHP programming language and a MySQL database. Key features include data management for regions, retailers, farmers, and farmer groups, fertilizer allocation, redemption, and stock and distribution reporting in graphical and tabular form. System testing results indicate that the application can simplify the recording and tracking of subsidized fertilizer distribution, increase transparency between relevant parties, and minimize data input errors common in manual systems. With this information system, the fertilizer distribution process becomes more structured and accountable, thus supporting the effectiveness of government subsidy programs in the agricultural sector.